273 Safety of research cores obtained from clinically indicated biopsies in the accelerating medicines partnership network. (April 2019) - Buyon, Jill; Belmont, Michael; Izmirly, Peter; Bornkamp, Nicole; Trad, Catherine; Bhan, Rohit; Robins, Kimberly; Clancy, Robert; Putterman, Chaim; Wu, Ming; Network, AMP
Abstract : Background: The Accelerating Medicines Partnership (AMP) is a public-private network comprising the National Institutes of Health, medical centers, biopharmaceutical companies and non-profit organizations. The Networks overarching mission is to develop SLE diagnostics and treatments via transcriptomic analysis of cells isolated from renal biopsies. This study addresses the safety of the research component of clinically indicated percutaneous kidney biopsies in anticipation of generalizing these results for real world clinical practice. We focused on one site (NYU METRO) for uniformity of data collection in which all biopsies were done by interventional radiology using an 18 gauge needle. Methods: Patients undergoing kidney biopsies to evaluate proteinuria exceeding 500 mg/day (based on uPCR) were consented to donate research tissue which was acquired via an extra pass or the use of a piece of a core with sufficient glomeruli available for both clinical evaluation and research. Adverse events (AE) within 30 days of biopsy were reported. Results: 98 patients with sufficient research kidney tissue have enrolled through the three Phases of AMP (0=technical, 1=technical translational, 2=ongoing full follow-up): 10 males, 88 females; 68 Non-Hispanic (69.4%), 30 Hispanic (30.6%); 19 Asian (19.4%), 32 Black (32.7%), 46 White (46.9%), 1 other (1.0%). Biopsy classes varied: 5 non-LN (5.1%), 1 Class I (1.0%), 5 Class II (5.1%), 21 Class III (21.4%), 16 Class IV (16.3%), 15 Class V (15.3%), 20 Class III/V (20.4%), 11 Class IV/V (11.2%), 3 Class VI (3.1%), 1 not yet determined. Research biopsy core lengths ranged from 4–19 mm. Eleven patients had an AE (research biopsy core lengths 5 13 mm); 8 were hematomas (only 6 had an extra pass specific for research). Of the 8 patients, 5 were hospitalized, 4 for the hematoma with 1 receiving a transfusion. Neither number of passes nor research core length predicted hematoma. All hematomas resolved within one week. The remaining 3 AEs were unrelated to the biopsy: 1 cardiac event-related death, 1 UTI, 1 fall. This site-specific frequency is similar to that being observed in the overall multisite ongoing Phase 2 AMP Network. Conclusions: Albeit this detailed report is limited to one site, it is consistent with the Network experience. These data support the feasibility and safety of obtaining a research core to bring personalized medicine to the management of LN. Funding Source(s): This work was supported by the Accelerating Medicines Partnership (AMP) in Rheumatoid Arthritis and Lupus Network. AMP is a public-private partnership (AbbVie, Arthritis Foundation, Bristol-Myers Squibb, Foundation for the NIH, Lupus Foundation of America, Lupus Research Alliance, Merck Sharp and Dohme, NIAID, NIAMS, Pfizer, Rheumatology Research Foundation, Sanofi, and Takeda Pharmaceuticals) created to develop new ways of identifying and validating promising biological targets for diagnostics and drug development. Funding was provided through grants from the National Institutes of Health (UH2-AR067676, UH2-AR067677, UH2-AR067679, UH2-AR067681, UH2-AR067685, UH2-AR067688, UH2-AR067689, UH2-AR067690, UH2-AR067691, UH2-AR067694, UM2-AR067678).